2018
DOI: 10.1016/j.actbio.2017.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and nanofibrous poly(l-lactic acid) scaffolds to promote the odontogenic potential of dental pulp cells in an inflammatory environment

Abstract: The regeneration potential of stem cells is dependent on their microenvironment. In this study, we investigated the effect of the microenvironment of dental pulp stem cells (DPSCs), including 3D structure of a macroporous and nanofibrous scaffold, the inflammatory stimulus lipopolysaccharide (LPS) and a biological molecule simvastatin, on their regenerative potential of mineralized dentin tissue. The results demonstrated that LPS upregulated inflammatory mediators and suppressed the odontogenic potential of DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 76 publications
4
56
0
Order By: Relevance
“…This corresponds well with the SV concentrations used in other studies (0.01, 0.1, 1 and 10 µM) investigating human odontoblast-like and dental pulp stem cells [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The mentioned studies examined different parameters of human cells, for instance expression levels of ALP-conversion rates and dentin matrix acidic phosphoprotein 1 (DMP-1) [ 29 , 30 , 31 , 35 , 36 ], dentin sialophosphoprotein (DSPP) [ 29 , 32 , 34 , 35 , 36 , 37 , 39 ], bone morphogenic protein 2 (BMP-2) [ 34 , 36 , 37 , 39 ], osteocalcin (OCN) [ 30 , 31 , 32 , 34 , 36 , 37 ], osteopontin (OPN) [ 30 , 31 ], osteonectin (ON) [ 29 , 31 ], Runx-2 [ 30 , 34 , 37 ], platelet endothelial cell adhesion molecule (PECAM-1) [ 31 ], mineralization [ 30 , 31 , 34 , 35 , 36 , 37 , 39 ] and viability [ 29 ...…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This corresponds well with the SV concentrations used in other studies (0.01, 0.1, 1 and 10 µM) investigating human odontoblast-like and dental pulp stem cells [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The mentioned studies examined different parameters of human cells, for instance expression levels of ALP-conversion rates and dentin matrix acidic phosphoprotein 1 (DMP-1) [ 29 , 30 , 31 , 35 , 36 ], dentin sialophosphoprotein (DSPP) [ 29 , 32 , 34 , 35 , 36 , 37 , 39 ], bone morphogenic protein 2 (BMP-2) [ 34 , 36 , 37 , 39 ], osteocalcin (OCN) [ 30 , 31 , 32 , 34 , 36 , 37 ], osteopontin (OPN) [ 30 , 31 ], osteonectin (ON) [ 29 , 31 ], Runx-2 [ 30 , 34 , 37 ], platelet endothelial cell adhesion molecule (PECAM-1) [ 31 ], mineralization [ 30 , 31 , 34 , 35 , 36 , 37 , 39 ] and viability [ 29 ...…”
Section: Discussionsupporting
confidence: 88%
“…The mentioned studies examined different parameters of human cells, for instance expression levels of ALP-conversion rates and dentin matrix acidic phosphoprotein 1 (DMP-1) [ 29 , 30 , 31 , 35 , 36 ], dentin sialophosphoprotein (DSPP) [ 29 , 32 , 34 , 35 , 36 , 37 , 39 ], bone morphogenic protein 2 (BMP-2) [ 34 , 36 , 37 , 39 ], osteocalcin (OCN) [ 30 , 31 , 32 , 34 , 36 , 37 ], osteopontin (OPN) [ 30 , 31 ], osteonectin (ON) [ 29 , 31 ], Runx-2 [ 30 , 34 , 37 ], platelet endothelial cell adhesion molecule (PECAM-1) [ 31 ], mineralization [ 30 , 31 , 34 , 35 , 36 , 37 , 39 ] and viability [ 29 , 33 , 34 , 35 , 36 , 37 ]. For these investigations, especially dental pulp cells [ 29 , 31 , 33 , 35 , 36 , 37 , 39 ], dental pulp stem cel...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a classic marker, NF‐κb plays a key role in the inflammatory response (Sethi et al, ). Expression of NF‐κb associated with PLLA was found to be a component of drug delivery system and causes no inflammation (Soares et al, ). However, in our precious study, NF‐κb expression associated with PLLA degradation extract was observed with dose‐dependency (Chen et al, ), which was confirmed by Western bolt in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…PLLA nanofiber architecture structurally simulates collagen fibers and directly modifies cell behaviours, including adhesion, proliferation, and differentiation. The regenerative potential of dental pulp cells/NF-PLLA constructs has been investigated in various studies 21. Thus, PLLA nanofibers were used as the in vitro structural biomimetic of the native nanotopography found in the ECM/stem cell niche in vivo.…”
mentioning
confidence: 99%